Experience in the Use of Smoke to Mask the Combat Operations of the Red Army Troops During the Great Patriotic War - A. О. Smirnov; G. Yu. Polyakova; D. E. Mutasov; E. V. Bondarenko (Вестник войск РХБ защиты)
The means of smoke camouflage made it possible to carry out many effective operations, while saving and saving many  soldiers' lives. The purpose of the work is to summarize the experience of using smoke to mask the combat operations  of the Red Army troops during the Great Patriotic War. Materials and research methods. In chronological order, we  analyzed documents stored in the Central Archive of the Ministry of Defense of the Russian Federation (Podolsk), field  manuals of the Red Army of that time, materials on various electronic resources and memoirs of participants in the  events. The discussion of the results. If the first year of the war, smoke screens were used to a limited extent only on the  Leningrad and Karelian fronts, then in the period from August 1942 to August 1943, 161 smoke screens were placed  only on the Kalinin front in order to secure the flanks, as well as divert the attention of the enemy and blind him , which  in many cases ensured the absence of irretrievable losses of personnel and combat vehicles. In 1943, the use of smoke became a means of ensuring crossings, for example, during the period of forcing the Dnieper River. The following data  speak of the scale of the use of smoke in 1944: in the second half of the year alone, 1,449 smoke screens were delivered  on a common front of 1,351 km. In April 1945, 630 smoke screens were delivered with a total front of 700.2 km, both  on the main and secondary directions. They were used for operational camouflage on an army front scale. Conclusion.  The facts of the use of masking smokes given in the review indicate that smokes were an active means of masking the  military operations of troops during the Great Patriotic War, the principles of their use can be used during a special  operation in Ukraine.